Persistent digestive haemorrhage due to high jejunal vascular malformation. - Matteucci, Pablo; Voelker, Ricardo; Alvarez, Carmelo; Araújo, Octasilio; Grillo, Bartolomé; Mariño, Ana (Cirugía del Uruguay, 1987)
The authors present the case of a 42 years old female wlth a jejunal vascular malformatlon type II of Moore, that caused reiterations of digestive bleedlng, -The procedures has been almed to establlsh a preoperallve dlag. nosls and the lntraoperative cenflrmatlon are pointed out. RÉSUMÉ